PENGARUH CSR, PROFITABILITAS TERHADAP NILAI PERUSAHAAN (STUDI: PERUSAHAAN MAKANAN MINUMAN DI BEI TAHUN 2018-2022) - Zulianda, Delvia; Riski, Defia (STKIP Persada Khatulistiwa Sintang, 2024)
Every business must ensure the sustainability of the company's survival, and one of the efforts that can be made is to strive to increase the company's value to sustain and grow. The value of a company can be determined through Corporate Social Responsibility (CSR) and Profitability factors. This study aims to determine the influence of CSR and profitability on the value of the company. Study: Food and Beverage Companies in the Indonesia Stock Exchange (BEI) for the years 2018-2022. This research is a quantitative descriptive study. The population in this study is food and beverage companies listed on the Indonesia Stock Exchange for the years 2018-2022. The data used is secondary data obtained from the official BEI website. Data analysis was conducted using the panel data regression method with the assistance of Eviews 12 software. The results of the study show that CSR has a positive effect on the value of the company because companies are able to manage their social responsibilities effectively. Meanwhile, profitability also has a positive effect on the value of the company because companies can generate net profit from sales with well-managed operational costs, ultimately increasing the value of the company.